Pengembangan Aplikasi Augmented Reality Berbasis Android Pada Pengenalan Tarian Adat Papua - Muhammad Hasbi Aliefiudin; Yuli Asriningtias (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Developing and introducing traditional Papuan dance has many ways of developing and introducing it. Currently, the only media used to introduce the appearance of Papuan traditional dances are print media, mass media and internet media, which in fact are 2-dimensional. People tend to feel bored when reading and seeing dances with 2D images, especially in printed media such as school textbooks. Therefore, Augmented Reality (AR) is a technology that can be used to introduce this traditional dance. AR systems on mobile devices have only recently become viable due to advances in tracking and computing. Through mobile devices and other AR devices it is possible to discover a number of new applications, in situations, knowledge and geographic information retrieval. The use of Android-based gadgets is one of the effectiveness ways to invite people to learn about culture. The Papuan Traditional Arts Culture learning application is created in moving images, dance photos, dance videos and musical instruments which can stimulate students' interest in learning, making it more interesting and easy to understand. This Android-based Augmented Reality interactive learning application uses marker based tracking media for interaction with users using a camera and was created using Unity and Vuforia software to run the application and Blender software to create the objects. The result of writing this study is the application of an Augmented Reality-based introduction application to traditional Papuan dances